1990
DOI: 10.1111/j.1365-2826.1990.tb00459.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical Localization of Glucagon‐Related Peptides in the Cerebral Ganglion of the Protochordate Ascidian, Styela plicata

Abstract: The central nervous system of the protochordate ascidian Styela plicata has been investigated by means of irnmunocytochemical techniques in order to localize peptides of the glucagon/secretin family. In particular, glucagon-and peptide histidine isoleucinecontaining neurons were localized in the cortex of the cerebral ganglion, and numerous nerve cell bodies containing vasoactive ntestinal polypeptide occurred mainly in the medullary zone. Moreover, coexistence of glucagon/peptide histidine isoleucine and gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In annelids, a sister clade of molluscs, immunoreactive PACAP-like peptides and receptors were identified in the CNS and peripheral nervous system (PNS) (Reglödi et al, 2000;Molnar et al, 2006;Boros et al, 2008Boros et al, , 2010Varhalmi et al, 2008). Similarly, in the bivalve mollusc the Mediterranean mussel (Mytilus galloprovincialis), immunoreactivity for VIP was detected in the mantle and in gastropod molluscs, VIP-like molecules were detected in the nervous system of the sea hare (Aplysia kurodai) and land snail (Helix pomatia) and in innate immune cells of two freshwater snails (Planorbarius corneus and Viviparus ater) (Kuramoto et al, 1985;Ottavianil and Cossarizza, 1990;Ottaviani et al, 1992;Kaufmann et al, 1995;Licata et al, 2003). In the nervous system of the pond snail (Lymnaea stagnalis) two VIP immunoreactive neurons were detected (Schot et al, 1981).…”
Section: Lophotrochozoansmentioning
confidence: 99%
See 1 more Smart Citation
“…In annelids, a sister clade of molluscs, immunoreactive PACAP-like peptides and receptors were identified in the CNS and peripheral nervous system (PNS) (Reglödi et al, 2000;Molnar et al, 2006;Boros et al, 2008Boros et al, , 2010Varhalmi et al, 2008). Similarly, in the bivalve mollusc the Mediterranean mussel (Mytilus galloprovincialis), immunoreactivity for VIP was detected in the mantle and in gastropod molluscs, VIP-like molecules were detected in the nervous system of the sea hare (Aplysia kurodai) and land snail (Helix pomatia) and in innate immune cells of two freshwater snails (Planorbarius corneus and Viviparus ater) (Kuramoto et al, 1985;Ottavianil and Cossarizza, 1990;Ottaviani et al, 1992;Kaufmann et al, 1995;Licata et al, 2003). In the nervous system of the pond snail (Lymnaea stagnalis) two VIP immunoreactive neurons were detected (Schot et al, 1981).…”
Section: Lophotrochozoansmentioning
confidence: 99%
“…In the nervous system of the pond snail (Lymnaea stagnalis) two VIP immunoreactive neurons were detected (Schot et al, 1981). Immunoreactive GCG/GLP and SCT was also detected in immune cells of the two freshwater snails (Ottavianil and Cossarizza, 1990;Ottaviani et al, 1992). In annelids, VIP-like positive cells were detected in the CNS of the leech (Hirudo medicinalis), earthworm (Lumbricus terrestres), oligochaete (Nereis diversicolor) (Sundler et al, 1977;Osborne et al, 1982), and planarian (Schistosoma mansoni) (Gustafsson, 1987).…”
Section: Lophotrochozoansmentioning
confidence: 99%
“…Our data showed that the leech PCSK1 is prominently expressed in the supraoesophageal ganglion, representing the brain of the leech. Given that many invertebrate peptide hormones, including those of the leech, are produced by neurosecretory cells of the brain (Grimmelikhuijzen, et al 1980;Engelhardt, et al 1982;Vigna, et al 1984;Pestarino 1990;van Heumen and Roubos 1990;Gomot, et al 1992;Meester, et al 1992;Sonetti, et al 1992;Kellner-Cousin, et al 1994;Kellner, et al 2002;Wang, et al 2007;Miller and Newmark 2012), these specialized Hau-pcsk1-expressing cells may well be some of the neurosecretory cells of the leech.…”
Section: Invertebrate Pcsk1 Orthologs Have Not Been Characterized In mentioning
confidence: 99%